Analisis Economico Del Control Biológico De La Araña Roja (Tetranychus Spp) En El Cultivo De La Rosa A Través De La Aplicación Del Hongo Entomopatogeno (Verticillium Lecanii) - Armando Esteban Espinoza Espinoza; Carla Sofía Arguello Guadalupe; José Luis Hidalgo Gallegos; Carlos Raúl Camacho Latorre; Homero Santiago Robalino Robalino (European Scientific Journal, ESJ, 2017)
The production of roses in Ecuador is an economic opportunity that has been increasing since the 1980's. Ecuador is the fourth country in the world with a comparative advantage in rose production. Its quality and variety of colors has positioned the Ecuadorian rose as one of the best in the world. The research aims to compare four control treatments of the red spider (Tetranychus spp). Three of them are controlled through biological control (Verticillium Lecanii), while one of them is through chemical control. It tries to identify which one is the most efficient and that has the greatest economic benefit when compared to the control costs of each treatment. The results show significant evidence on T4 (chemical control), which is not only the most efficient in controlling mites at all stages of development. Also, it proves to be the least costly and it therefore provides greater profitability to the company.